COPD exacerbations: management and hospital discharge - Reis, A . J. (2018)
Chronic Obstructive Pulmonary Disease (COPD) is a serious pulmonary condition. Many patients experience exacerbations and some require Emergency Room visits and hospitalization. In Portugal, hospitalizations due to COPD between 2009 and 2016 decreased by 8%, but they still represented 8049 hospitalized patients in 2016. Appropriate management of COPD exacerbations presents a clinical challenge and, in order to guide therapy, it is important to identify the underlying cause; however, this is not possible in about a third of severe COPD exacerbations. There are several diagnostic tools that can be used to assess an exacerbation and its severity, which will in turn guide treatment, and prognostic scores should be used to predict the risk of future exacerbations. After an exacerbation is appropriately managed, a suitable discharge plan should be prepared. This should generally include reclassification of the patient according to GOLD criteria, optimization of pharmacological therapy, management of comorbidities, patient (or caregiver) education on the correct use of medications, referral to a Pulmonology Outpatient Clinic, if they are not already attending one, and a smoking cessation and respiratory rehabilitation program. In this paper, we will focus on the pharmacological strategies for the management of COPD exacerbations, risk stratification and a hospital discharge plan proposal.